Evaluasi Kinerja Dosen dengan Pendekatan Metode AHP dan BORDA - Muh. Nurtanzis Sutoyo; Nur Ihsan; Basrawi, Basrawi; Agus Nasir (Prosiding SISFOTEK, 2023)
This research aims to investigate the evaluation of faculty performance by utilizing a combined approach of the Analytic Hierarchy Process (AHP) and the Borda Method. The primary objective of this study is to develop a more structured, objective, and inclusive evaluation framework for assessing faculty performance. The AHP method is employed to address the complexity of determining the weights of evaluation criteria and sub-criteria, while the Borda Method provides a platform for various stakeholders to express their assessments in a participatory manner. This study is conducted using a qualitative research approach. Data is collected through surveys administered to students, colleagues, and administrators to provide evaluations of faculty performance based on predetermined criteria. The research results indicate that the combined approach of AHP and Borda is capable of offering a more accurate and holistic depiction of faculty performance. The AHP method assists in reducing subjectivity in weight determination, while the Borda Method facilitates the inclusion of opinions from various stakeholders.